The political thought of Thomas Sankara and its contemporary relevance - Kabwato, Levison M (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
On 4 August 1983, a thirty-three year-old army captain seized power in Burkina Faso and embarked on what can be described a revolutionary journey. Over the next four years, until his assassination in 1987 the government, led by Captain Thomas Sankara, attempted to redeem Burkina Faso from the clutches of neo-colonialism. Through popular mobilisation and organisation, infrastructure (schools, hospitals, bridges) was built, millions of children were vaccinated and diseases such as river blindness were eliminated. Women, long-subjugated by patriarchal systems took up space and led their own initiatives in freedom, including holding senior roles in the public service. On the international stage, practical solidarity was extended to countries either fighting or threatened by neo-colonialism despite the fact that Burkina Faso was poor and was itself threatened by France and her lackeys. What Sankara inherited in August 1983, twenty-three years after Burkina Faso's independence, was a fragile neo-colonial state which was not allowed by dominant imperialist interests to set an example of what true independence means. So, in just four years, it was all over. Sankara was assassinated by his comrades and the revolutionary project he had led came to a halt. The tragedy of Sankara was the tragedy of all those attempts at revolution which occur before mass movements have had the opportunity to develop and organise themselves independently of the state. Despite this, it is apparent today that Sankara has been influential on current political movements and parties in Africa, from Burkina Faso to South Africa. One of these political movements is the Economic Freedom Fighters (EFF) in South Africa. This half-thesis is an investigation of Sankara's political thought. It also examines the extent to which his answers to questions of nationalism and pan-Africanism both matched and differed from his predecessors. To accomplish the latter, a brief but critical analysis of the writings of AmÃlcar Cabral, Frantz Fanon, Kwame Nkrumah is made.
Keywords: Sankara, Thomas; Sankara, Thomas -- Influence; Burkina Faso -- Politics and government -- 1960-1987; Cabral, AmiÌ lcar, 1924-1973; Fanon, Frantz, 1925-1961; Nkrumah, Kwame, 1909-1972